Paradise Found: Nature in America at the Time of Discovery - Raymond Pierotti (Ethnobiology Letters, 2011)
Review of Paradise Found: Nature in America at the Time of Discovery. Steve Nicholls. 2009. University of Chicago Press, New York and London. Pp. 536. ISBN10: 0226583406 ISBN13: 978-0226583402.